Discontinuous Galerkin for the radiative transport equation - Guermond, Jean-Luc; Kanschat, Guido; Ragusa, Jean C. (Recent Developments in Discontinuous Galerkin Finite Element Methods for Partial Differential Equations, 2014)
This note presents some recent results regarding the approximation of the linear radiative transfer equation using discontinuous Galerkin methods. The locking effect occurring in the diffusion limit with the upwind numerical flux is investigated and a correction technique is proposed.